Thermodynamic Performance Study of Cascade Cooling Systems on Cruise Ships with Mixed Working Fluids and Operating Parameters - Fajri Ashfi Rayhan; Deva Natasya (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The cooling system is an important component on cruise ships to maintain engine operating temperatures and operational reliability. However, conventional cooling systems still have limitations in terms of energy efficiency and high thermodynamic losses. This study aims to analyze the performance of cascade cooling systems on cruise ships with variations in mixed working fluids, temperatures, pressures, and mass flow rates. The analysis was conducted using an energy and exergy approach to evaluate the Coefficient of Performance (COP), exergy efficiency, and exergy destruction. The study was conducted on a modified two-stage cascade cooling system. The working fluids analyzed include R22/R404A, R290/R404A, and R290/R600a. The results show that a decrease in mass flow rate in the high-temperature cycle increases the COP value, while an increase in temperature in Heat Exchanger Y increases exergy efficiency. The R22/R404A combination produced the highest exergy efficiency, while the hydrocarbon-based combination showed potential for COP improvement. This study demonstrates that optimizing operating parameters and selecting the appropriate working fluid can improve the energy efficiency of cascade refrigeration systems on cruise ships.